PENGARUH SUPERVISI AKADEMIK KEPALA SEKOLAH DAN HASIL PENILAIAN KINERJA GURU TERHADAP KINERJA GURU PENDIDIKAN AGAMA ISLAM DI SEKOLAH MENENGAH PERTAMA NEGERI KOTA BENGKULU - Syahrul Syahrul (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2020)
Teacher performance is the  main  Task and  function, This is reflected in the  appearance, academic ability and the  ability of the  profession to be a teacher means  being  able to manage teaching in the  classroom  and  educating students beyond  the  classroom  with the  best  even  the  teachers have  met  the  academic level professionalism. But  in  reality  on the  ground in general is still a lot of teachers are  less effective in carrying  out  its duties.  Therefore, the  problem in this research are: Are there academic supervision  effect principals on  performance of PAI teacher? and  Is there PKG results on  performance teacher? and  Is there an academic supervising  principals and  PKG results  together on  the  performance of PAI teacher in junior  high  school  in Bengkulu City?, further the  objectives of this study are: 1. To explain  the  academic Supervising  Principal Influence on  the  performance of Islamic education teachers (PAI);  2. To explain  the  results  PKG Effect  of PAI teacher against  performance teacher; 3. To  explain  how the  implementation of the  performance of PAI teachers in junior  high  school  in Bengulu City. This research is a quantitative research that  aims to determine the  effect of independent variables on the  dependent variable. The  method used is a survey method, which is to measure symptoms exist without  investigating why these  symptoms  exist, with questionnaires. Research  results  show that  the  Supervision  of Academic  Principal (X1)  Positive direct  impact  on  teacher performance (y), amounting to 0.918. or by 91.80%.  Further Results Teacher Performance Assessment (X2)  has no effect on teacher performance (y) of -307. or by -30.70%. Furthermore Principal Academic  Supervision  (X1),  and  the  Teacher Performance Assessment (X2)  a positive direct  impact  on teacher performance (y) of 0.845 or 84.50%.